Medullary Thyroid Carcinoma With Exon 2 p.L56M RET Variant: Clinical Particular Features in Two Patients - Paragliola, Rosa M.; Lovicu, Rosa M.; Papi, Giampaolo; Capoluongo, Ettore; Minucci, Angelo; Canu, Giulia; Pontecorvi, Alfredo; Corsello, Salvatore M. (Frontiers in Endocrinology, 2018)
RET (REarranged during Transfection) proto-oncogene variants are essential for the development of familial and sporadic forms of medullary thyroid carcinoma (MTC). The most frequent variants are usually located in exons 10, 11, and 13 through 16 of the RET gene. We report two cases of apparently sporadic MTC associated with the variant in exon 2 of RET gene. Patient 1, a 62-year old man who had undergone adrenalectomy for a 5 cm pheochromocytoma, was screened for type 2 multiple endocrine neoplasia (MEN 2) which showed elevated basal and post-intravenous calcium gluconate calcitonin levels. A fine needle aspiration biopsy confirmed the suspicion of MTC. The patient underwent total thyroidectomy and lymphadenectomy, and the histology showed C-cell hyperplasia with medullary microcarcinoma. Patient 2, a 57 years old woman, underwent total thyroidectomy for toxic multinodular goiter. Pre-operative fine needle aspiration biopsy had shown benign features, while basal calcitonin levels were only borderline increased. Final histology revealed medullary multifocal microcarcinoma. Genetic testing for RET protoncogene on DNA extracted from peripheral blood was performed in both patients and a missense variant on exon 2 (c.166C>A, p.L56M) was identified. To our knowledge, these are the first time two cases of MTC associated to RET p.L56M variant. Interestingly, one patient had also a pheochromocytoma suggesting a possible pathogenetic role of this variant in the genesis of MEN2A. While the association of this variant with MTC or MEN2A has been never reported, it has been described in association with Hirschsprung’s disease.